2015
DOI: 10.1260/1747-9541.10.6.1001
|View full text |Cite
|
Sign up to set email alerts
|

Expert Coaches' Perceptions of Athlete Performance Optimization

Abstract: The purpose of the study was to engage expert coaches in a reflective process exploring their perceptions of distinguishing features of athletes they consider optimal performers. Fifteen national and/or Olympic level coaches were interviewed. Developed through a content analysis of the data, elite coach descriptions provided a preliminary profile of elite athlete performance optimization centred on five main themes: a rational approach to training and performance; exhibiting sustained passion and commitment to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Jackson and Roberts (1992) found that participants’ worst performance was associated with worrying about the outcome, the third strand of research on competition. Several studies of elite athletes (Cohn, 1991), coaches of elite athletes (Tracey, Elcombe, Culp, Carlson, & Petitpas, 2015), and other participants (Privette & Bundrick, 1997; van de Pol, Kavussanu, & Ring, 2012) have yielded similar findings. On the basis of these and similar studies, researchers have concluded that training athletes on psychosocial skills can increase performance outcomes in competition and that competition is associated with specific positive motivational states (Greenspan & Feltz, 1989; Harmison, 2006; Martin, Vause, & Schwartzman, 2005).…”
Section: Positive Psychology Competition and Outstanding Performancementioning
confidence: 64%
“…Jackson and Roberts (1992) found that participants’ worst performance was associated with worrying about the outcome, the third strand of research on competition. Several studies of elite athletes (Cohn, 1991), coaches of elite athletes (Tracey, Elcombe, Culp, Carlson, & Petitpas, 2015), and other participants (Privette & Bundrick, 1997; van de Pol, Kavussanu, & Ring, 2012) have yielded similar findings. On the basis of these and similar studies, researchers have concluded that training athletes on psychosocial skills can increase performance outcomes in competition and that competition is associated with specific positive motivational states (Greenspan & Feltz, 1989; Harmison, 2006; Martin, Vause, & Schwartzman, 2005).…”
Section: Positive Psychology Competition and Outstanding Performancementioning
confidence: 64%
“…T here has been growing interest in the role of mindfulness in athletic performance. 1 The most commonly used approach is Mindfulness-Acceptance-Commitment (MAC) including a package specifically designed for athletes. 2 MAC emphasises the importance of a person-centred, non-judgemental awareness of inner and outer stimuli in improving performance with beneficial outcomes in semi-professional football, martial arts and para-sports including improved psychological well-being (PWB).…”
mentioning
confidence: 99%
“…Given elite-level coaches generally experience time-related challenges due to internally and externally imposed pressures [ 1 , 4 , 8 ], coaches may not consider the management of their own mental health as a competitive priority when compared with other influences (e.g. tactical advantages) [ 47 ]. Exploring the link between mental health and coaching effectiveness could therefore have potential value from a performance and ecological perspective.…”
Section: Introductionmentioning
confidence: 99%